Ketidakadilan Hukuman Mati Mary Jane Veloso Ditinjau dari Mazhab Hukum Alam - Michelle Alycia Sutanto (CV Rewang Rencang, 2025)
The case of Mary Jane Veloso, a Filipino domestic worker sentenced to death in Indonesia for drug trafficking, highlights systemic failures in ensuring justice, legal certainty, and utility. Despite claims of being an unwitting victim of human trafficking, she faced trial with inadequate legal counsel and translation, raising concerns about due process and fairness. Viewed through Natural Law Theory, her case demonstrates a disregard for universal morality and human dignity. The analysis underscores the urgent need for legal reform in Indonesia to address procedural flaws, recognize trafficking contexts, and prioritize rehabilitation over retribution in line with human rights standards.